DRINKING WATER QUALITY RESEARCH IN KARSAVA MUNICIPALITY VILLAGES - Buravcevs, Artūrs; Laizāne, Ināra (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
In the work is displayed and analyzed data of drinking water quality in Karsava Municipality villages. The sampling places were mapped and described. Are summarized detection methods of drinking water quality parameters testing – ammonia ion concentration, summary iron concentration, turbidity, pH and water conductivity. Those parameters values displayed in a transparent manner graphs, and then analyzed. Was made a correlation between the summary iron concentration and turbidity, as well as turbidity depending on summary iron concentration.